Nutritional and quality evaluation of hyperbaric stored fresh cheeses - Ricardo V. Duarte; Susana Casal; Ana M. Gomes; Ivonne Delgadillo; Jorge A. Saraiva (Food Chemistry Advances, 2023)
Cow's and goat's fresh cheese (FC), two highly perishable dairy products, were stored under hyperbaric storage at room temperature (HS/RT, 50–100 MPa) and compared with refrigeration (RF, 4 °C), for 60 days.Under HS/RT (≥75 MPa), FCs presented a more stable volatile organic and fatty acid profiles, and reduced lipid oxidation rate, particularly for cow's FC, resembling more to FC prior storage, contrarily to refrigerated cheeses. No changes were observed for total protein, but free amino acids increased over time after 60 days at 75/RT of 13- and 16-fold, and at 100/RT of 14- and 8-fold, respectively in cow's and goat's FC, which may have contributed to increased protein digestibility (5.2%) observed for goat's FC after 60 days at 100/RT.In general, the results indicate the overall increased preservation performance achieved by HS/RT for cow's and goat's FC when compared with RF, slowing down FC matrix degradation, possibly leading to considerable shelf-life extension.